(untitled) (Journal of the College of Basic Education, 2022)
Some aspects of the immune response associated with infection with the Toxoplasma gondii parasite were investigated among aborted women attending the Imam al-Kadhimin Hospital, peace be upon them both, in Baghdad. The total number of 170 women, whose ages ranged between 16-42 years, for the period from the beginning of March to the end of June 2015, and who suffer from problems in Pregnancy, all patients were subjected to a diagnostic ELISA test for the detection of IgG and IgM antibodies. Based on its results, the group of patients was divided into 100 aborted women infected with toxoplasmosis, and 45 aborted women for other reasons without toxoplasmosis. They were counted as a positive control group with 25 married women who did not suffer from toxoplasmosis. Any previous abortion and not infected with toxoplasmosis, and was called the negative control group.